Conservative Treatment of Stage IA1 Adenocarcinoma of the Uterine Cervix during Pregnancy: Case Report and Review of the Literature - Francesco Sopracordevole; Diego Rossi; Jacopo Di Giuseppe; Marta Angelini; Pierino Boschian-Bailo; Monica Buttignol; Andrea Ciavattini (Case Reports in Obstetrics and Gynecology)
Microinvasive adenocarcinoma (MIAC) of the uterine cervix is rare in pregnancy. Published data on conservative treatment of MIAC both in pregnant and nonpregnant women are scarce. A conservatively treated case of MIAC in a 13-week-pregnant woman after a diagnosis of atypical glandular cells (AGC) on pap smear at the 6th week of pregnancy is presented. The problems of suspected adenocarcinoma in situ (AIS) on biopsy and MIAC on cone biopsy in pregnancy, as well as the risks and benefits of a conservative treatment are discussed. After colposcopic guide laser cervical conization and expression of informed consent the patient underwent followup and vaginal delivery at 40 weeks plus 3 days of gestation. In this case, no obstetric complication has been recorded after the cervical conization, and after a followup of 18 months the patient was alive and free of disease, with negative results as far as pap smear, colposcopy, HPV status, and cervical curettage are concerned. In a stage Ia1 disease of endocervical type, with clear margins and without lymph-vascular space invasion, cervical conization performed during the second trimester may be considered a definitive and safe treatment, at least up to delivery, after expression of informed consent by the woman.